Penerapan Pendekatan Persentase Penyelesaian Dalam Pengakuan Pendapatan Dalam Bisnis Jasa Kontraktor - Eugenia Audrey Hiendrata (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study investigates the application of the percentage of completion (PPP) method in revenue recognition in contractor services companies. The PPP method has become a common choice for contractors to accurately recognize revenue in construction projects. In this context, this research analyzes various aspects related to the use of the PPP method in recognizing income, including the advantages, disadvantages, and factors that influence its application. Data were obtained through interviews with project managers and analysis of related documents. The research results highlight the importance of a good understanding of the PPP method and appropriate adjustments to project characteristics and market conditions to increase accurate revenue recognition in the contractor services business.